2016
DOI: 10.2460/javma.248.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic meningoencephalitis and disseminated infection caused by Balamuthia mandrillaris in a Western lowland gorilla (Gorilla gorilla gorilla)

Abstract: CASE DESCRIPTION A 22-year-old male gorilla (Gorilla gorilla gorilla) housed in a zoo was evaluated for signs of lethargy, head-holding, and cervical stiffness followed by development of neurologic abnormalities including signs of depression, lip droop, and tremors. CLINICAL FINDINGS Physical examination under general anesthesia revealed a tooth root abscess and suboptimal body condition. A CBC and serum biochemical analysis revealed mild anemia, neutrophilia and eosinopenia consistent with a stress leukogram,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Direct examination of CSF was not reported to be useful in any case of B. mandrillaris infection in animals; the inflammatory response detected in CSF is considered to be nonspecific for amoebic infections. 8,9 Diagnosis of encephalitis from B. mandrillaris has not been made in biopsy samples from animals, to our knowledge, likely as a result of the clinical risk of obtaining samples in cases of encephalitis of presumed infectious origin.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Direct examination of CSF was not reported to be useful in any case of B. mandrillaris infection in animals; the inflammatory response detected in CSF is considered to be nonspecific for amoebic infections. 8,9 Diagnosis of encephalitis from B. mandrillaris has not been made in biopsy samples from animals, to our knowledge, likely as a result of the clinical risk of obtaining samples in cases of encephalitis of presumed infectious origin.…”
mentioning
confidence: 99%
“…One report used IHC to highlight amoebic organisms but used antibodies that were not specific for a particular amoeba group. 8 Histochemical staining was not used routinely to detect amoebic infections in animals; a few reports used Giemsa and/or periodic acid-Schiff to highlight the organisms in areas of severe inflammation, 8 whereas others suggested that these stains did not adequately highlight the pathogens. 11 Indirect immunofluorescence from tissue has been used to discriminate among B. mandrillaris, N. fowleri, and Acanthamoeba spp.…”
mentioning
confidence: 99%
See 3 more Smart Citations